2013
DOI: 10.1007/s00170-013-5167-7
|View full text |Cite
|
Sign up to set email alerts
|

An image acquisition system for real-time seam tracking

Abstract: Gas metal arc welding (GMAW) process is one of the most widespread welding processes used in industries for their excellent quality, reliability, productivity, and cost-effectiveness. To develop an automatic GMAW system, vision capability in the system is a necessary component supplying real-time information about weld pool and seam tracking. In this research work, an automatic seam tracking system is presented, where the automatic tracking of welding path and torch positioning are performed by a newly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…the images captured by the vision system, are processed in order to give as output the desired features. Based on these features, process parameters such as welding torch position, torch speed, or electrical parameters can be determined based on a suitable decision making procedure, such as a neurofuzzy approach [6][7][8].…”
Section: The Image Processingmentioning
confidence: 99%
“…the images captured by the vision system, are processed in order to give as output the desired features. Based on these features, process parameters such as welding torch position, torch speed, or electrical parameters can be determined based on a suitable decision making procedure, such as a neurofuzzy approach [6][7][8].…”
Section: The Image Processingmentioning
confidence: 99%
“…Hence, the seam center that is detected cannot be immediately used to rectify the position of the heat source. Nele et al [17] reported a tracking error of 0.66 mm due to the lag distance of 50 mm between the weld torch and the vision sensor (CCD camera). In practical scenarios where the welding direction changes frequently rather than walking a straight line [17,18], the tracking error is significant.…”
Section: Introductionmentioning
confidence: 98%
“…Nele et al [17] reported a tracking error of 0.66 mm due to the lag distance of 50 mm between the weld torch and the vision sensor (CCD camera). In practical scenarios where the welding direction changes frequently rather than walking a straight line [17,18], the tracking error is significant. An alternative solution to this problem is to perform seam detection and actual welding in two different passes [19].…”
Section: Introductionmentioning
confidence: 98%
“…The real intelligent welding encompasses at least three parts. First, guidance of initial welding positions [3,4] should be implemented. Next, accurately weld seam tracking for different weld joints [5,6] has to be included and third, real-time weld defect detection [7][8][9] and welding quality control must be carried out.…”
Section: Introductionmentioning
confidence: 99%